Quality of life and self-esteem of women who practice Pilates - Oliveira, Francineide Rocha de Aguiar; Guará, Olga Lorena Maluf; Fróes, Aline; Souza, Marcelo Cardoso de; Caldas, Renata Trajano Jorge (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The Pilates Method has been excelled as an activity that values the functional capacity, coordination, strength, balance and cooperates for the well-being of those who practice it. Objective: This study evaluated the quality of life and self-esteem of women practicing the Pilates method. Methods: Descriptive and cross-sectional study with a sample of 60 women, 30 practitioners of the method (Pilates group) and 30 non-practitioners (control group). For data collection were applied a socio-demographic data sheet and two other instruments: the SF-36, a generic quality of life questionnaire and the Rosenberg Self-esteem Scale, an instrument for measuring self-esteem. Results: Participated in the study 60 women, divided into Pilates group and control group. The groups were considered statistically similar with respect to age, schooling, marital status, work, housing and BMI. Regarding quality of life, there were only statistically significant differences between the groups for the general health domain (p≤0.001) and emotional aspects (p=0.001) with better results for the Pilates group. For the self-esteem, there was no statistical difference between the groups (p=0.05). Conclusion: Women who practice Pilates present some aspects of quality of life (general health and emotional aspects) in superiority to those who do not practice it.